The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3889/oamjms.2021.7859
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health Application to Support Family Caregivers in Recurrent Stroke Prevention: Scoping Review

Abstract: BACKGROUND OF THE STUDY: Caregivers play a vital role in continuum care for stroke patients. Involvement of caregivers in stroke care was important. With the advancement of information technology and the rapid growth worldwide in cell-phone use and internet connectivity, additional evidence may be needed in the use of mobile applications to support caregivers in stroke care. AIM OF THE STUDY: The aims of this review was to identify existing mobile application designed to support family caregivers of peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
(133 reference statements)
1
5
0
Order By: Relevance
“…Regarding the availability of services for caregivers, the features mentioned by the study participants were comparable to those in previously published reviews ( 17 , 18 ). However, they emphasized the need for a healthcare service directory to connect caregivers with essential assistance, such as ambulance and home care services, as well as the importance of financial support due to significant expenses related to patient wellbeing, which is consistent with the findings of a local study on stroke management mobile applications for informal caregivers ( 49 ).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Regarding the availability of services for caregivers, the features mentioned by the study participants were comparable to those in previously published reviews ( 17 , 18 ). However, they emphasized the need for a healthcare service directory to connect caregivers with essential assistance, such as ambulance and home care services, as well as the importance of financial support due to significant expenses related to patient wellbeing, which is consistent with the findings of a local study on stroke management mobile applications for informal caregivers ( 49 ).…”
Section: Discussionsupporting
confidence: 78%
“…Numerous non-pharmacological treatment modalities, such as psychoeducational and psychosocial information, and skill-building interventions have been adopted and delivered on various digital platforms (including mobile health applications) to assist and empower stroke caregivers ( 14–17 ). A scoping review of seven articles regarding mHealth apps for family caregivers in preventing recurrent stroke revealed that many apps used video education, exercise reminders, access to stroke-related information, and feedback mechanisms ( 17 ). The studies were conducted in seven countries, namely the United States, Pakistan, the Netherlands, Korea, India, China, and Sweden, and all studies were conducted to test the feasibility of the apps in question ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it should be noted that there are few web-based or digitally available tools. In a review, Firmawati et al identified mobile applications for family caregivers of people with stroke as supportive [94]. Studies have found evidence that mHealth or eHealth tools for family caregivers have an impact on the burden of care [95].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there are also a number of mobile applications available to support these ICs. A scoping review found that these apps provide help in three main areas: caregiver support, barriers, and informal caregiver support [ 36 ]. In addition, the mHealth tools for ICs of stroke survivors include several functionalities such as information resources, risk assessment, remote monitoring, data sharing or reminders [ 37 ].…”
Section: Introductionmentioning
confidence: 99%